ПЕДАГОГІЧНІ ЗНАННЯ В ЗМІСТІ ПЕДАГОГІЧНОЇ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2006)
The necessity of including of different pedagogic knowledge in the content of pedagogic training of students o f pedagogic university and its structuring on the base of different approached is proved.